International Students in American Pathway Programs: Learning English and Culture through Service-Learning - Miller, Julie; Berkey, Becca; Griffin, Francis (Journal of International Students, 2015)
As the number of international students studying in the United States continues to grow, the body of literature about service-learning in English Language Learning (ELL) curricula is growing in tandem. The primary goal of this paper is to explore how service-learning impacts the development and transition of pathway program students in the United States. Authors present recent demographic shifts in ELL student education, a concise introduction to pathway programs, an overview of literature about service-learning with international students, and theoretical and practical factors to consider for facilitators of Learning English and Culture through Service-Learning (LECSL) based on data from 250 students at Northeastern University.